Evaluating the Performance of Internal Control under the Electronic Accounting System in Saudi Private Universities. Case Study of Private Colleges in Gassim 2021 - Yousif, Adil Mohamed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
Internal control is considered an essential part of comprehensive control and its importance, because it is considered the first line of defense in preventing repelling and limiting the risks that may be exposed to it through the process of ensuring the correctness of Accounting Information for what is recorded in the records, protecting the colleges assets, raising the efficiency of employees, and encouraging them to adhere to administrative and financial policies. The study aims to know the extent of reliance on accounting information in the internal control process in light of the use of electronic accounting in private colleges in Gassim, in addition to knowing the extent to which the internal auditor is familiar with understanding and evaluating electronic accounting in private colleges in Gassim.The importance of the study stems from the importance of the research stems from the importance of internal control and its role in maintaining the integrity and validity of the financial statements, and therefore this requires several procedures and requirements carried out by the authority responsible for preparing the financial statements and auditing, whether it is internal auditing or external auditing, thus contributing to identifying weaknesses and strengths in The process of internal control in private colleges in Gassim. The study followed the analytical descriptive approach and the case study approach and method. Primary information was collected through a questionnaire and secondary information was collected through books, references, periodicals and publications. The time limit for the study year 2021.The most important results of the study proved that the accounting operations were completed quickly through the electronic accounting programs and thus led to the quality of the financial reports, and that the electronic accounting programs contributed to achieving the degree of safety and reliability and ensuring the outputs of the electronic accounting system , and there is a periodic review of the internal control system by the Department of Internal Audit in the colleges.
Keywords: internal control; electronic accounting; private universities; Saudi Arabia